A Comparative Review of Mobile and Non-Mobile Games for Language Learning. (December 2021) - Su, Fan; Zou, Di; Xie, Haoran; Wang, Fu Lee
Recent studies have increasingly investigated the effectiveness of both mobile and non-mobile digital game-based language learning. To gain an in-depth understanding of the differences in the effectiveness of mobile and non-mobile games, we compared studies from January 2000 to August 2020 investigating mobile game-based language learning (MGBLL) and non-mobile game-based language learning (NMGBLL). Sixty-four articles were analyzed from four aspects: game types, game elements, target languages, and learning outcomes. The results showed that (a) gamification, simulation games, and immersive games were applied most; (b) all games possessed the game elements of goals or rules; (c) the most investigated target languages were English and Chinese; and (d) the most discussed learning outcomes were language acquisition and psychological/affective state. The similarities and differences between MGBLL and NMGBLL were also identified. The current review provides an overview and in-depth analysis of mobile and non-mobile games for language learning, guiding practitioners to select appropriate digital games to cater to specific language teaching goals. Future directions of research are also discussed.